Bharat Footwear Limited discount coupons - Shah, Bhavin J., (SAGE Business Cases., 2018)
The case presents a customer experience while purchase of a pair of shoes in the upmarket retail outlet Bharat Footwear Limited (BFL), in Ahmedabad, India. While negotiating the purchase of the pair of shoes, the customer is offered a 20% discount coupon meant for BFL shareholders, for a split consideration in the ratio of 60 (buyer) and 40 (agent). The customer must decide if they should accept the deal and leads to a discussion as to whether BFL should continue the promotion.